Applying Biotechnology and Bioengineering to Pediatric Lung Disease: Emerging Paradigms and Platforms - Colvin, Kelley L.; Yeager, Michael E. (Frontiers in Pediatrics, 2015)
Pediatric lung diseases remain a costly worldwide health burden. For many children with end-stage lung disease, lung transplantation remains the only therapeutic option. Due to the limited number of lungs available for transplantation, alternatives to lung transplant are desperately needed. Recently, major improvements in tissue engineering have resulted in newer technology and methodology to develop viable bioengineered lungs. These include critical advances in lung cell biology, stem cell biology, lung extracellular matrix, microfabrication techniques, and orthotopic transplantation of bioartificial lungs. The goal of this mini-review is to engage the reader’s interest with regard to these emerging concepts and to stimulate their interest to learn more. We review the existing state of the state of lung tissue engineering, and point to emerging paradigms and platforms in the field. Finally, we summarize the challenges and unmet needs that remain to be overcome.